Computer-aided design of short-lived phosphorescent Ru(II) polarity probes. (March 2019) - Ielasi, Guido; Alcover, Gerard; Casellas, Josep; de Graaf, Coen; Orellana, Guillermo; Reguero, Mar
Abstract: Fluorescent polarity probes are usually based on intramolecular charge transfer excited states of selected dyes, the behavior of which in different solvents is traditionally rationalized by the well-known Lippert-Mataga treatment of the "general solvents effect". Less often transition metal coordination complexes are used as luminescent probes, even though the spectroscopic properties of these dyes are usually dependent on the environment. This is the case of Ru(II) polypyridyls, which are good candidates to develop robust sensitive polarity probes because of their lowest-lying metal-to-ligand charge transfer triplet emissive state, provided their chelating ligands structure is judiciously tuned. The aim of this work has been to design a computational strategy to forecast the behavior of polarity-sensitive Ru(II) complexes without the need to prepare a large set of candidates. In particular, we have analysed a number of complexes derived from [Ru(bpy)3 ] 2+ by introducing different pairs of substituents in the 4, 4′ positions of one of the three equivalent 2, 2′-bipyridine (bpy) moieties. In this way, we have investigated if a direct relationship may be established between the electronic features of the substituent and the Stokes shift sensitivity to the solvent polarity. Our computational data satisfactorily agree with our experimental results, but they demonstrate that only by explicitly performing the calculation of the Stokes shift in different media for each candidate, it is possible to select the best Ru(II) dyes to be used as polarity probes. Graphical abstract: Highlights: The Stokes shift of 60 Ru(II) polypyridyl complexes was computed by DFT methods. Their 3 MLCT (metal-to-ligand charge transfer) emission depends on solvent polarity. Computer calculations account for the "anti" Lippert-Mataga behavior observed. Further novel polarity-sensitive dyes may be prepared based on the calculations.